DEVELOPING CREATIVE THINKING SKILLS AND CREATIVE ATTITUDE THROUGH PROBLEM BASED GREEN VISION CHEMISTRY ENVIRONMENT LEARNING (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The purpose of this research is to build creative thinking skills and creative attitude of students through a model of problem-based lectures Environmental Chemistry (PBL) Green Chemistry visionary. Mixed methods research design experimental models embedded with pretest-posttest control group were used in this study, and the differences between assumed initial end-tests as the effects of the treatment. Creative thinking skills measured by the essay tests, non test while the creative attitude is measured from the completed questionnaires consisting of positive and negative statements of markers creative attitude. Data measurement N-gain of creative thinking skills for the control and experimental group were 0.40 and 0.71, while the creative attitude were 0.08 and 0.34. Improved tests of creative thinking skills or creative attitudes were analyzed by t-test. Implementation of research findings indicate environmental chemistry lecture- problems based Green Chemistry vision can improve thinking skills and of creative student.